Neuropeptide Y Is an Immunomodulatory Factor: Direct and Indirect - Chen, Wei-can; Liu, Yi-bin; Liu, Wei-feng; Zhou, Ying-ying; He, He-fan; Lin, Shu (Frontiers in Immunology, 2020)
Neuropeptide Y (NPY), which is widely distributed in the nervous system, is involved in regulating a variety of biological processes, including food intake, energy metabolism, and emotional expression. However, emerging evidence points to NPY also as a critical transmitter between the nervous system and immune system, as well as a mediator produced and released by immune cells. In vivo and in vitro studies based on gene-editing techniques and specific NPY receptor agonists and antagonists have demonstrated that NPY is responsible for multifarious direct modulations on immune cells by acting on NPY receptors. Moreover, via the central or peripheral nervous system, NPY is closely connected to body temperature regulation, obesity development, glucose metabolism, and emotional expression, which are all immunomodulatory factors for the immune system. In this review, we focus on the direct role of NPY in immune cells and particularly discuss its indirect impact on the immune response.